FAMILIARIZATION WITH INFORMATION ABOUT MODERN BIOINFORMATIC DATABASES - Amonov Abdullaziz Uktamovich (Web of Journals Publishing, 2024)
The article reveals the role of bioinformatics in the development of biological sciences, in particular genetics, genomics and transcriptomics. The role of bioinformatics as a science is described, which includes the creation and application of computational tools, algorithms, databases for storing, extracting, managing and analyzing biological information
Keywords: bioinformatics, genomics, genetics, transcriptomics, alogorhythm, program, statistics, DNA, RNA.